Employee Performance Measurement in Teleworking Using Balanced Scorecard - Sunu Sugi Arso; Sfenrianto Sfenrianto; Mochamad Wahyudi (International Journal of Electrical and Computer Engineering (IJECE), 2018)
Key Performance Indicator (KPI) must be aligned with the development of the organization. PT. Mitra Intregrasi Informatika (MII) in its development decided to change the traditional way of work to modern telework. This encourages companies to adjust employee’s KPI from the traditional way of work turns in to telework. In order to perform KPI measurement of its employees based on teleworking, this research uses balanced scorecard method approach that is by taking into account financial, customer, and internal business process and learning and growth perspective. The results of this study are the design proposal KPI employees to accommodate telework at the company. Then KPI employee test results showed an increase in the average value of the employee KPI of 0.295 points (9.47%) of the old KPI. Thus, it is recommended to the company to implement the employee KPI.